(untitled) (Revista da Tulha, 2021)
Around 1987, Brazilian pianist Sônia Goulart published an LP entirely dedicated to piano pieces of composer Fructuoso Vianna (1896-1976), entitled Fructuoso Vianna - obras quase inéditas para piano. In an interview given to XXXX, the performer talks about this experience, along with the importance of Fructuoso Vianna for Brazilian music. She also reflects on how much Vianna’s compositions were part of concert programs by women performers, mainly in 20th century Brazil.